The Place of the Lost Architectural and Urban Planning Heritage in the Modern Environment of Ukrainian Cities - Gaidar, Volodymyr (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
The study examines the problem of presenting the lost architectural and urban planning heritage in the modern environment of Ukrainian cities. Currently, in our historical cities, we have a significant number of lost valuable architectural structures and complexes that are not known to society. These are unique objects that had historical, urban planning, scientific and restoration value, their place and role in the volume-spatial structure of cities was often key. Today, these objects are critically lacking for the formation of a coherent picture of the perception of the historical environment. The historical environment today is not perceived as it was originally intended by the creators of cities. For the most part, it was the lost components of historical cities that contained significant national, cultural-artistic, architectural-historical value. Such objects as castles, palaces, fortresses, sacred, public, recreational, residential complexes formed national identity and were material symbols of the entire Ukrainian people. On the example of a lost sacred building – the Greek Catholic church of the 17th century. in the historical city of Ivano-Frankivsk, a variant of the symbolic identification of a lost valuable object is presented. The developed and implemented project “Square with a memorial sign in honor of the first Ukrainian Church of the Holy Resurrection (XVII century) in Ivano-Frankivsk” is a composition of volumetric and spatial symbolic identification of the Ukrainian church, which helps to form a complete picture perception of the city’s architectural and urban planning heritage. The object is located in a formed historical environment, successfully complements it and symbolizes the Ukrainian heritage of the past.